Pengembangan Aplikasi Pengajuan dan Pengelolaan Alat Tulis Kantor pada SMP Pembinaan Pangkalpinang - Perdana Putra, Adrian (Jurnal Media Informatika dan Teknologi, 2023)
SMP (Junior High School) Pembinaan is one of the institutions providing private elementary and secondary level education in the City of Pangkalpinang. The request for and management of Office Stationery (OS) at SMP Pembinaan is still conventional where submissions are made using WhatsApp or orally. In addition, the request still uses a notebook that was written after the OS was given to the requester. Sometimes the administration section forgets to write down the taken OS in the OS taking notebook. This resulted in a discrepancy between the amount of stock according to the records and those in the warehouse. To overcome this, an Android-based OS request and management application is needed that is interconnected and integrated with one another. The proposed application is also equipped with a push notification feature to notify the administration section if a new request comes in so that it can be processed immediately. Models, methods, and software development tools used in this study are Extreme programming, object-oriented methods, and Unified Modeling Language. The application can help SMP Pembinaan employees in submitting OS. In addition, the proposed application also makes it easier for the administration in managing OS as well as responding to OS requests.